Does environmental regulation induce improved financial development for green technological innovation in China? - Zhou, Xiaoxiao; Du, Juntao (Journal of environmental management, 2021)
The effect of environmental regulations on the nexus between financial development and biased technological innovation is a prerequisite for optimizing systems of environmental and financial policies to gain sustainable development goals (SDGs) in emerging markets. Drawing on China's city-level data from 2003 to 2018, we established econometric models and obtained the following empirical results. Financial development (FD) can promote energy- and environmental-biased technological progress, but, owing to the inverted U-shaped relationship, economic development, and resource endowment, the impact that FD has on biased technological progress is heterogeneous; unreasonable FD will also hinder green technological progress. Threshold model shows that with the improvement of environmental regulation, the impact of energy- and environmental-biased technological progress is also increasing. The development of green finance under SDGs is an important driving force in green technological progress. Finally, we offer suggestions to optimize environmental and financial policymaking and implementation from a government intervention perspective. [Display omitted] •It is important to optimize environmental and financial policies to gain SDGs.•Environmental policies are affected by technological and financial developments.•Financial development (FD) promotes energy- and environmental-technological growth.•Due to an inverted U-shaped relationship biased FD hinders green technology growth.•Green finance development under SDGs will drive green technological progress.